Inclusion of cover crops in cropping sequences with soybean predominance in the southeast of the Humid Argentine Pampa - Martinez, Juan Pablo; Barbieri, Pablo Andres; Sainz Rozas, Hernan Rene; Echeverria, Hernan Eduardo (2017)
The incorporation of a cover crop (CC) may be an alternative to increase soil carbon (C) and nitrogen (N) supply in crop sequences with a high frequency of soybean. The aims of this study were (i) to determine shoot biomass production, C and N contents in the CC under two N additions, (ii) to evaluate the effect on soybean grain yield of including a CC, and (iii) to evaluate the water productivity of the crop sequences. Crops were evaluated during three growing seasons of a long-term field trial under no tillage on Typic Argiudoll in Balcarce, Buenos Aires, Argentina. Mean CC shoot biomass was 6.6 Mg ha-1 yr-1 for N-fertilized and 5.2 Mg ha-1 yr-1 for non-fertilized treatments. Mean C and N accumulation in the CC shoot biomass were 2.8 Mg C ha-1 yr-1 and 131 kg N ha-1 yr-1 in N-fertilized treatments, and 2.3 Mg C ha-1 yr-1 and 67 kg N ha-1 yr-1 in nonfertilized treatments. Soybean grain yield ranged from 2.4 to 4.3 Mg ha-1. In two out of the three growing seasons, soybean grain yield was greater (p<0.05) for crop sequences that included a CC. Water productivity was higher (p<0.05) in crop sequences with a CC and even higher when they were N-fertilized. The inclusion of a CC preceding soybean in crop sequences is an alternative to improve soil C and N budgets and would be a promising strategy to increase productivity and cropping system sustainability in this region.